2023
DOI: 10.3390/jcm12072588
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Experience of a Novel Pulsed Solid-State Thulium:YAG Laser during Percutaneous Nephrolithotomy

Abstract: Introduction: Laser lithotripsy during Mini-PCNL is one treatment option in urinary stone disease. In recent years, a new era in stone treatment has been initiated with the introduction of new pulsed thulium lasers. The aim of this study was to investigate the safety and efficacy of laser lithotripsy with a new pulsed solid-state thulium:YAG laser during mini-PCNL. Materials and methods: All patients, regardless of stone size, who were treated with a Mini-PCNL using the new pulsed thulium laser were prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The findings of this study are pivotal for the broader future implementation of the p-Tm:YAG in clinical routine, considering that studies found in the literature so far have presented data based on non-human stone lithotripsy models (BegoStone, plaster of paris, gypsum/glass) [ 13 , 14 , 22 ], or if conducted in humans did not investigate laser effects on different human urinary stone compositions [ 16 ]. It is of particular interest to note that the p-Tm:YAG was amenable to lithotripsy of cystine stones, akin to the Ho:YAG and TFL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are pivotal for the broader future implementation of the p-Tm:YAG in clinical routine, considering that studies found in the literature so far have presented data based on non-human stone lithotripsy models (BegoStone, plaster of paris, gypsum/glass) [ 13 , 14 , 22 ], or if conducted in humans did not investigate laser effects on different human urinary stone compositions [ 16 ]. It is of particular interest to note that the p-Tm:YAG was amenable to lithotripsy of cystine stones, akin to the Ho:YAG and TFL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these preliminary reports were based on lithotripsy models using artificial Bego Stones—and not human urinary stones—with the primary outcome being stone ablation efficiency rather than evaluation of stone dust per se. Two recent in vivo studies evaluated the clinical efficacy and safety of the p-Tm:YAG on case series of patients undergoing retrograde intrarenal surgery [ 15 ] and mini-percutaneous nephrolithotomy [ 16 ]. Both studies conclude that the p-Tm:YAG seems very promising, with patients included having a range of stone densities, although no information regarding exact differing stone compositions was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the pulsed Thulium:YAG laser has been proposed as a further alternative to the Ho:YAG, with promising stone dusting proprieties ( 23 ). Two clinical studies are available to date and reveal the pTm:YAG as an efficient and safe laser for lithotripsy ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The global prevalence of urinary stone disease treatment has shown a steady rise [ 1 ] Within the armamentarium of urinary stone management, the laser has emerged as a cornerstone for lithotripsy in endourological procedures [ 2 ]. The trajectory of laser technology has witnessed a progressive evolution, transitioning from the established holmium: yttrium-aluminum-garnet (Ho: YAG) laser with pulse modulation to the advent of thulium fiber laser (TFL) and, more recently, the innovative pulsed thulium: YAG (p-Tm: YAG) laser [ 3 ]…”
Section: Introductionmentioning
confidence: 99%